Incidents related to safety in mental health facilities in Kenya - Kamaru Edith Kwobah; Sitienei Robert Kiptoo; Florence Jaguga; Felicita Wangechi; Saina Chelagat; Francis Ogaro; WK Aruasa (BMC, 2023)
Abstract Background Both patients and health care providers working in mental health facilities witness high rates of incidents that have the potential to jeopardize their safety. Despite this, there are few studies that have documented the kind of incidents that are experienced, or explored the potential contributors to these incidents, and solutions that would result in better safety. This study explored various types of safety related incidents occurring in mental facilities in Kenya, perceived contributing factors, and recommendations for improve. Methods This qualitative descriptive study was carried out between December 2019 - February 2020. It included 28 mental health staff across 14 mental health unit spread across the country. Results All the participants reported having personally experienced an incident that threatened their safety or that of the patients. Most of the respondents (24/26. 91.67%) admitted to have experienced verbal aggression while 54.17%, (n = 24) had experienced physical assault. Participating health care workers attributed the safety incidents to poor infrastructure, limited human resources, and inadequate medication to calm down agitated patients. Suggested solutions to improve patient safety included; improving surveillance systems, hiring more specialized healthcare workers, and provision of adequate supplies such as short-acting injectable psychotropic. Conclusion Incidents that threaten patient and staff safety are common in mental health facilities in Kenya. There is need to strengthen staff capacity and reporting mechanisms, as well as invest in infrastructural improvements, to safeguard patient and staff safety in mental health facilities in Kenya.